Mycological researches in Victoria land terrestrial ecosystems - S. Onofri; S. Tosi; S. Riess; L. Zucconi; PERSIANI, Anna Maria; MAGGI, Oriana (Edizioni Universitarie Patavine, 1994)
About 45 species was isolated by Antarctic soils and studied by SEM.